Exploring a Chemotactic Role for EVs from Progenitor Cell Populations of Human Exfoliated Deciduous Teeth for Promoting Migration of Naïve BMSCs in Bone Repair Process - Lin Luo; Steven J. Avery; Rachel J. Waddington (Stem Cells International)
Mobilization of naïve bone marrow mesenchymal stromal cells (BMSCs) is crucial to desired bone regeneration in both orthopedic and dental contexts. In such conditions, mesenchymal progenitor cell populations from human exfoliated deciduous teeth (SHEDs) present advantageous multipotent properties with easy accessibility which makes them a good candidate in both bone and periodontal tissue regeneration. Extracellular vesicles (EVs) are a functional membranous structure which could participate in multiple cell interactions and imitate the biological functions of their parenting cells largely. To assess their ability to mobilize naïve BMSCs in the bone repair process, Nanosight Tracking Analysis (NTA) and Enzyme-Linked Immunosorbent Assays (ELISA) were performed to illustrate the composition and functional contents of EV samples derived from SHEDs with different culturing time (24 h, 48 h, and 72 h). Afterwards, the Boyden chamber assay was performed to compare their capacity for mobilizing naïve BMSCs. One-way analysis of variance (ANOVA) with a post hoc Turkey test was performed for statistical analysis. SHEDs-derived EVs collected from 24 h, 48 h, and 72 h time points, namely, EV24, EV48, and EV72, were mainly secreted as exosomes and tended to reform into smaller size as a result of sonication indicated by NTA results. Moreover, different EV groups were found to be abundant with multiple growth factors including transforming growth factor-β1 (TGF-β1), platelet-derived growth factor (PDGF), insulin-like growth factor-1 (IGF-1), and fibroblast growth factor-2 (FGF-2) given the detections through ELISA. Boyden chamber assays implied the migratory efficiency of BMSCs driven by EVs at varying concentrations. However, the results showed that migration of BMSCs driven by different EV groups was not statistically significant even with chemotactic factors contained (P>0.05). Taken together, these data suggest that EVs derived from SHEDs are secreted in functional forms and present a potential of mobilizing naïve BMSCs, which may propose their relevance in assisting bone regeneration.